2011
DOI: 10.1179/147842210x12754747500685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 7·5 vol.-% water vapour on oxidation of nickel based alloy between 900 and 1100°C

Abstract: A Ni based SY 625 alloy was oxidised at 900, 1000 and 1100uC under dry and wet conditions. Water vapour has little effect on the oxidation rate and scale composition. At 900 and 1000uC, the outer scale is composed of Cr 2 O 3 , and a continuous NbNi 4 -Ni 3 Mo subscale is found at the oxide/ alloy interface. At 1100uC, the scale is composed of an outer chromia scale and an internal CrNbO 4 subscale. Nevertheless, the oxide scale morphology differs between dry and wet conditions. Under dry conditions, the oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The number and size of light-colored precipitates in the grain boundaries increased with increasing sintering temperature and EDS results suggesting the formation of MC type NbC [12]. where the grain boundary carbide precipitates are located, the compositional formula is suggested to be M 6 C. This phase tends to be formed in alloys rich in refractory metals such as Mo and W [12,33]. It is reported that M 6 C-type carbides form as grain boundary precipitates in alloys containing more than 6-8% Mo or W [18]; in the current study, powder with 8.9 wt.-% Mo is used.…”
Section: Density Measurementsmentioning
confidence: 86%
See 1 more Smart Citation
“…The number and size of light-colored precipitates in the grain boundaries increased with increasing sintering temperature and EDS results suggesting the formation of MC type NbC [12]. where the grain boundary carbide precipitates are located, the compositional formula is suggested to be M 6 C. This phase tends to be formed in alloys rich in refractory metals such as Mo and W [12,33]. It is reported that M 6 C-type carbides form as grain boundary precipitates in alloys containing more than 6-8% Mo or W [18]; in the current study, powder with 8.9 wt.-% Mo is used.…”
Section: Density Measurementsmentioning
confidence: 86%
“…The evaporation of Cr 2 O 3 as CrO 3 gas at temperatures above 1000 °C is reported in [12]. Thus, Cr 2 O 3 decomposes into Cr and CrO 3 , then CrO 3 evaporates and the Cr that is left behind from the oxide decomposition dissolves into the matrix [33]. In Ni-based superalloys, different types of oxide phases may occur.…”
Section: Phase Formation Study By Xrdmentioning
confidence: 97%
“…All the connecting tubes are maintained at 100°C in order to avoid any water condensation out of the furnaces. A schematic drawing of the rig has been provided in a previous paper [34]. Similar gas humidifiers were used either for TGA and wet in situ DRX (MRI chamber).…”
Section: Methodsmentioning
confidence: 99%
“…A schematic drawing of the rig is provided in a previous paper. 34 Similar gas humidifiers were used either for TGA, wet in situ XRD (MRI chamber) and thermal cycling tests in a tubular furnace. Dry air testing was performed in flowing air at atmospheric pressure.…”
Section: Methodsmentioning
confidence: 99%